Stem Cell Regulators - Litwack, Gerald (Vitamins and hormones, 2011)
First published in 1943, Vitamins and Hormones is the longest-running serial published by Academic Press. The Editorial Board now reflects expertise in the field of hormone action, vitamin action, X-ray crystal structure, physiology and enzyme mechanisms. Under the capable and qualified editorial leadership of Dr. Gerald Litwack, Vitamins and Hormones continues to publish cutting-edge reviews of interest to endocrinologists, biochemists, nutritionists, pharmacologists, cell biologists and molecular biologists. Others interested in the structure and function of biologically active molecules like hormones and vitamins will, as always, turn to this series for comprehensive reviews by leading contributors to this and related disciplines. This volume focuses on stem cell regulators. *Longest running series published by Academic Press *Contributions by leading international authorities.